Excise Tax, Education, And Income Factors: Impact On Cigarette Consumption - Wisanggeni, Zufar Lutfi; Muchtar, Masruri; Sihombing, Pardomoan Robinson (WIM Solusi Prima, 2024)
Tobacco consumption remains high despite its numerous negative impacts. In this study, the author aims to identify the variables influencing cigarette consumption This study aims to identify the variables influencing cigarette consumption. The independent variables include excise tax rates, gross tertiary education enrollment, and per capita income. This research employs a quantitative method utilizing panel data regression in all provinces of Indonesia for 2018-2022. The results indicate that both excise tax rates and per capita income postively impact cigarette consumption. Gross tertiary education enrollment, on the other hand, are the sole variable exhibiting a negative influence on cigarette consumption. This study contributes to existing research literature and offers potential avenues for further investigation.